New sesquiterpenes and benzofuran derivatives from the aerial parts of Asterothamnus centrali-asiaticus. Issue 32 (11th August 2016) - Wang, Yan-Ming; Zhao, Jian-Qiang; Zhou, Shuang-Yan; Yang, Jun-Li; Yao, Xiao-Jun; Tao, Yan-Duo; Mei, Li-Juan; Shi, Yan-Ping
Abstract: Phytochemical investigation on Asterothamnus centrali-asiaticus afforded four new sesquiterpenes, asterothamnones A–D (1 –4 ), and three new benzofuran derivatives (5 –7 ) together with ten known compounds (8 –17 ). Their structures were elucidated using 1D and 2D NMR and X-ray diffraction analyses. Compounds1 –4 were verified to be unusual eudesmane sesquiterpenes possessing 4, 6-dien-3-one or 1, 4, 6-triene-3-one conjugated system. The absolute configurations of compounds1 –8 were established by means of calculated electronic circular dichroism (ECD). Furthermore, all isolates were evaluated for their cytotoxic and anti-oxidant activities. Results showed that10, 12 and, 14 exhibited cytotoxic activity against HepG2 cancer cells and14 displayed cytotoxicity against MGC-803 cancer cells. Compounds10 and17 showed anti-oxidant effect. Graphical abstract: